Excess mortality in Aspirin and Dipyrone (Metamizole) co-medicated in patients with cardiovascular disease: a nationwide study. (3rd October 2022) - Polzin, A; Dannenberg, L; Helten, C; Metzen, D; Duecker, C; Marschall, U; L Hoest, H; Hennig, B; Petzold, T; Jung, C; Levkau, B; Zeus, T; et al.
Abstract: Background: Pain is a serious issue in our aging society. Metamizole is one of the most commonly used analgesics. In addition, metamizole has been shown to attenuate the pharmacodynamics response to aspirin as measured by platelet function tests. However, the extent to which this laboratory effect translates to clinical outcome in patients is unknown. Methods: We conducted a nationwide analysis based on health insurance database including 9.2 million patients in Germany. All patients with a cardiovascular event in 2014 and subsequent secondary prevention with aspirin were followed up for 36 months. Inverse probability of treatment weighting (IPTW) analysis was performed to examine mortality rates between patients on aspirin-metamizole co-medication and aspirin medication alone. Myocardial infarction (MI) and stroke/transient ischemic attack (TIA) events were also documented. Results: 26, 200 patients received continuous aspirin medication alone and 5, 946 received co-medication with aspirin and metamizole. In the IPTW analysis, significantly increased mortality was observed in the co-medication group (15.6% vs. 24.4%, hazard ratio (HR)=1.66, 95% confidence interval (CI) 1.56–1.76; p<0.0001). MI and stroke/TIA were also increased (MI: 1, 370 [5.2%] vs. 355 [5.9%]; HR=1.18, 95% CI 1.05–1.32; p=0.0066, relative risk (RR) 1.14, absolute risk increase (ARI) 0.71%, number needed to harm (NNH) 140. Stroke/TIA: 1, 901 [7.3%] vs. 506 [8.5%]; HR=1.22, 95% CI 1.11–1.35; p<0.0001, RR 1.17, ARI 1.21%, NNH 82). Conclusion: In this nationwide observational study, aspirin-metamizole co-medication was associated with excess mortality. This was partly due to ischemic events (MI and stroke/TIA), which were also more frequent in the co-medication patients. Therefore, metamizole should be used with caution in aspirin-treated patients for secondary prevention Funding Acknowledgement: Type of funding sources: None.